More Than Serving Food on the Table: Understanding Household Relations of a Woman as a Factory Worker - Franceline Anggia (Department of Anthropology Faculty of Cultural Sciences Universitas Gadjah Mada, 2022)
Western modern theorists have long perceived intimate relations as unproductive, irrational, and unrelated to the economy. This kind of approach neglects nuanced ties that might be preconditions of women’s participation in the paid workforce. Consequently, women workers’ perspectives in defining their work have often been overlooked. This study will critically examine an industrial woman worker’s way of defining work-decision by exploring how a desire to maintain intimate relations in the household serves as a crucial precondition for women’s participation in the paid workforce. Though precariousness pervades a woman worker’s work condition, a chance to work as a factory worker also becomes a source of self-esteem and self-confidence. This study shows how nuanced and intimate relations within a household which involve performative acts of gender as a mother and a wife constitute a woman worker’s insistence on working in a precarious condition. This research departs from an ethnographic-based approach relying on participant observation and in-depth interviews with a textile factory woman worker in Yogyakarta. Data analyses are processed based on thematic interpretation of field notes, transcript of the interview, and review of relevant literature regarding feminist theoretical understandings of the economy.